Obtención de biodiesel a partir de aceite vegetal usado en frituras de alimentos utilizando diferentes concentraciones de lejía - Santana Coronel, Verónica Fernanda (2019)
The objective of this research project is to produce biodiesel from vegetable oil used in cooking. The objective was to obtain biodiesel from vegetable oil used in food frying using different concentrations of bleach. A completely randomized experimental block design with factorial arrangement AxB and three repetitions was used to compare: Factor A (concentrations of bleach) and Factor B (temperature) and the effect it exerts when interacting the two factors, which allowed to determine differences in terms of performance and combustion. To establish the effects between the levels of the treatments, the Tukey significance test was applied (p <0.05). The analysis of the data was carried out using the statistical package STATGRAPHICS, to define competitive parameters of performance and characteristics suitable for the combustion process, analyzes were performed as: acidity, calorimetry, absorbance, transmittance, turbidity density, boiling point and viscosity. This research concludes that the different treatments comply in a certain way with the authors of the research carried out in the production of biodiesel, besides presenting characteristics similar to other biodiesel of good quality. According to the results obtained, the two percentages of bleach (0.8 -1%) can be used, as well as giving better results in calorimetry and viscosity. While at temperatures (50 - 60 ° C) I have better results in density and boiling point. Regarding the performance results, the treatment (a0b0) with 49% of biodiesel obtained better results. Key words: vegetable oil, combustion, transesterification, yield